'A really hostile environment': Adiaphorization, global policing and the crimmigration control system. (May 2020) - Bowling, Ben; Westenra, Sophie
This article examines institutional practices designed to control criminalized migrants in the UK and advances three arguments. First, these practices have evolved, since the early 1970s, into a bespoke 'crimmigration control system' distinct from the domestic criminal justice system. Second, this system is directed exclusively at efficient exclusion and control; through a process of adiaphorization, moral objections to the creation of a 'really hostile environment' have been disabled. Third, the pursuit of the criminalized immigrant—a globally recognized 'folk devil'—provides a vital link between domestic and global systems of policing, punishment and exclusion. The UK crimmigration control system is an example of wider processes that are taking place in institutions concerned with the control of suspect populations across the globe.